Genome-wide identification and expression analysis of the regulator of chromosome condensation 1 gene family in wheat (Triticum aestivum L.) - An, Xia; Zhao, Shuqi; Luo, Xiahong; Chen, Changli; Liu, Tingting; Li, Wenlue; Zou, Lina; Sun, Chendong (Frontiers in Plant Science, 2023)
Wheat (Triticum aestivum L., 2n = 6x = 42, AABBDD) is the world’s most widely-cultivated crop and an important staple food for humans, accounting for one fifth of calories consumed. Proteins encoded by regulator of chromosome condensation 1 (RCC1) are highly conserved among eukaryotes and consist of seven repeated domains that fold into a seven-bladed propeller structure. In this study, a total of 76 RCC1 genes of bread wheat were identified via a genome-wide search and their phylogenetic relationship, gene structure, protein conserved domain, chromosome localization, conserved motif and transcription factor binding sites were systematically analyzed using the bioinformatics approach, to indicate the evolutionary and functional features of these genes. The expression patterns of 76 TaRCC1s family genes in wheat under various stresses were further analyzed and RT-PCR verified that RCC1-3A (TraesCS3A02G362800), RCC1-3B (TraesCS3B02G395200) and RCC1-3D (TraesCS3D02G35650) were significantly induced by salt, cold and drought stresses. Additionally, the co-expression network analysis and binding sites prediction suggested that Myb-7B (TraesCS7B02G188000) and Myb-7D (TraesCS7D02G295400) may bind to the promoter of RCC1-3A/3B and upregulate their expression in response to abiotic stresses in wheat. The results have furthered our understanding of the wheat RCC1 family members and will provide important information for subsequent studies and use of RCC1 genes in wheat.